Integrasi Manajemen Dakwah dalam Bimbingan Islam untuk Meningkatkan Keterampilan Sosial Penyalahguna NAPZA - Fadilah, Nurul; Al Kahfi, Al Kahfi (BINA' AL-UMMAH, 2024)
Drug abuse among adolescents is a pressing problem in Indonesia, with adverse impacts on the mental, spiritual and social health of users. This research explores the application of dakwah management integration in Islamic counselling guidance, specifically through prayer and dhikr, in improving the social skills of drug abusers at Yayasan Lentera Mutiara, Mataram. The research method used is descriptive qualitative, producing data in the form of written or spoken words from observation. The research was conducted at Yayasan Lentera Mutiara Mataram, West Nusa Tenggara, regarding the application of Islamic Counselling Guidance in drug abuse rehabilitation. Primary data was obtained from interviews with three clients (AS, JF, AN) who were inpatients for at least 3 months, and two counsellors with at least 2 years of experience. Secondary data includes written documents and actions. The results showed that Islamic counselling guidance through prayer and dhikr practices contributed significantly to the improvement of personality, more controlled social behaviour, good communication, and religious values of the clients. The programme creates a holistic rehabilitation approach that brings together spiritual and social aspects to help drug abusers undergo a comprehensive recovery process.